1999
DOI: 10.1046/j.1365-2958.1999.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular characterization of the first autolytic lysozyme of Streptococcus pneumoniae reveals evolutionary mobile domains

Abstract: SummaryA biochemical approach to identify proteins with high af®nity for choline-containing pneumococcal cell walls has allowed the localization, cloning and sequencing of a gene (lytC ) coding for a protein that degrades the cell walls of Streptococcus pneumoniae. The lytC gene is 1506 bp long and encodes a protein (LytC) of 501 amino acid residues with a predicted M r of 58 682. LytC has a cleavable signal peptide, as demonstrated when the mature protein (about 55 kDa) was puri®ed from S. pneumoniae. Biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(150 citation statements)
references
References 69 publications
4
146
0
Order By: Relevance
“…N-terminal sequence determination showed that Met 1 was removed under the overexpression and purification conditions used. The specific activity of the purified protein on [ 3 H]cholinelabeled pneumococcal cell walls was 1.1 ϫ 10 5 units mg Ϫ1 under optimal conditions (25 mM sodium acetate, pH 5.5, 37°C), which was slightly lower than the value reported for the Cpl-1 lysozyme at equivalent conditions (6).…”
Section: Cpl-7 Purificationmentioning
confidence: 64%
See 1 more Smart Citation
“…N-terminal sequence determination showed that Met 1 was removed under the overexpression and purification conditions used. The specific activity of the purified protein on [ 3 H]cholinelabeled pneumococcal cell walls was 1.1 ϫ 10 5 units mg Ϫ1 under optimal conditions (25 mM sodium acetate, pH 5.5, 37°C), which was slightly lower than the value reported for the Cpl-1 lysozyme at equivalent conditions (6).…”
Section: Cpl-7 Purificationmentioning
confidence: 64%
“…However, the cell wall binding region (CWBR) of Cpl-1, made of six tandem copies of ϳ20 amino acid residues plus a terminal tail, belongs to the family of pneumococcal choline-binding modules (5). Its lytic activity is thus conditioned by the presence of choline moieties in pneumococcal teichoic and lipoteichoic acids and becomes inhibited at high choline concentrations (IC 50 ϭ 2 mM) (1,6). In contrast, Cpl-7 degrades pneumococcal cell walls containing either choline or ethanolamine and retains full activity even in the presence of high concentrations of these amino alcohols (7).…”
mentioning
confidence: 99%
“…The LytB endo-␤-Nacetylglucosaminidase is involved in daughter cell separation (37), whereas the LytC 1,4-␤-N-acetylmuramidase increases the rate of autolysis at 30°C (38). The deacetylation of the glycan strand GlcNAc residues could be a way of controlling the activities of these potentially autolytic enzymes.…”
Section: Identification Of N-deacetylated Amino Sugars In the Pneu-mentioning
confidence: 99%
“…9). Of these, the major autolysin (LytA) is an amidase (9), whereas the two minor peptidoglycan hydrolases (LytB and LytC) function as a glucosaminidase (10) and a lysozyme (11), respectively. LytA and LytC are responsible of the autolytic release of toxins like pneumolysin, which by irritating the host tissues allows pneumococcus to gain access to the bloodstream.…”
mentioning
confidence: 99%